Penggunaan Media Wordwall English Learning Mystery Box Untuk Meningkatkan Kemampuan Anak Mengenal Bahasa Inggris Dasar di Tk Gmim 15 Tandurusa Kota Bitung - Lumente, Fadila; Tiwow, Mieke Farny; Tolukun, Threesje (Jurnal Ilmiah Wahana Pendidikan, 2023)
Research This research is motivated by the lack of children's knowledge of basic English. The purpose of introducing basic English is to develop the child's skills and language acquisition in children, especially foreign languages and to determine children's communication intelligence in the future. to determine children's communication intelligence in the future in the current globalisation era. the current era of globalisation. The type of research used in this study This type of research used in this study is classroom action research referring to the Kemmis and McTaggart model which model which consists of four stages, namely: 1. planning, 2. implementation, 3. observation, and 4. Reflection. The research subjects were students in GMIM 15 Tandurusa Kindergarten, Bitung City, totalling 10 children. Bitung City which totalled 10 children. Data collection techniques used are observation and documentation. The results showed a good change The results showed a good change in cycle I which reached 65.0% of learning completeness, after cycle II action research the results obtained increased by 95.0%. cycle II action research the results obtained increased to 95.0% with an increase of 30.0%. with an increase of 30.0%. From the results obtained, it means that the objectives of This research has been successful. Based on the research, it can be concluded that conclusion that the media wordwall english learning mystery box can improve children's ability to recognise basic English.